Pengaruh Work life balance Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi Pada Perawat RS XYZ) - Raymond; Soegeng Wahyoedi; Melitina Tecoalu (Syntax Idea)
In the ongoing era of globalization, human resource management plays a very important role in efforts to improve organizational performance. Currently, research is focusing on evaluating the performance of nurses at Hospital "XYZ" (RS "XYZ") due to the downward trend in performance in this context. Based on data analysis, it was concluded that work motivation, work-life balance, and working environment conditions have the potential to affect nurses' job performance and satisfaction. The purpose of this study was to explore the relationship between work motivation, work-life balance, and work environment with the performance and job satisfaction of nurses in "XYZ" Hospital. The method used in this study was a survey by distributing questionnaires to nurses at "XYZ" Hospital. The results of the data analysis showed that work motivation, work-life balance, and working environment conditions significantly affected the performance and job satisfaction of nurses at "XYZ" Hospital. The implication of these findings is that the management of "XYZ" Hospital needs to pay special attention to these aspects to improve the performance and job satisfaction of nurses.